Presenting Fake Figures: A Tool to Teach Effective Scientific Figure Design - Verónica A. Segarra (American Society for Microbiology, 2013)
As trained scientists, we become adept not only at analyzing and understanding figures in the scientific literature, but also at designing figures to effectively represent our own data and findings. As educators, we strive to pass on these skills to our students, some of whom will ultimately become scientists themselves. Conveying the principles of effective figure design can be challenging, particularly when students have had little exposure to the process of reading scientific literature, much less writing a piece of scientific literature. Improvisational activities in the classroom reinforce teaching goals such as spontaneity, risk-taking, creativity, communication skills, team-building, and critical thinking (2). Indeed, improv training for scientists is becoming more common, helping scientists to communicate more spontaneously about their work and connect with their audience (1). In this article, we present an improvisational game that can aid in the teaching of effective scientific figure design. This “Present-a-Fake-Figure Exercise” is applicable to both the classroom and laboratory settings. In this learning activity, students improvise presenting fake scientific figures to an audience of their peers. These fake figures are prepared beforehand by the instructor and exemplify the do’s and don’ts of scientific figure design. Some of the learning outcomes of the activity include (1) identifying what makes a scientific figure cohesive, easy to analyze, and reader-friendly, and (2) identifying strategies that are useful in the design of a multi-panel figure to convey a scientific story.